2008
DOI: 10.1002/bmc.1039
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organic acids in urine by solid‐phase microextraction and gas chromatography–ion trap tandem mass spectrometry previous ‘in sample’ derivatization with trimethyloxonium tetrafluoroborate

Abstract: A method for the determination of the organic acids directly in the urine employing derivatization with trimethyloxonium tetrafluoroborate as a methylating agent and sequential extraction by head space and direct immersion/solid phase microextraction is reported. Furoic acid, hippuric acid, methylhippuric acid, mandelic acid, phenylglyoxylic acid and trans, trans muconic acid contained in urine and proposed by the American Conference of Governmental Industrial Hygienists as biological exposure indices were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 34 publications
(41 reference statements)
2
41
0
Order By: Relevance
“…Therefore, the constant of distribution estimated from physicochemical tables or by using the structural unit contribution method can anticipate trends in SPME analysis. The KH of the TBC-dimethylether, acetylacetone-PFB-oximes and TBBC-methyl-bis-oxime derivatives were 1.3, 71 52 and atm cm 3 /mol, which were in agreement with that reported by Pacenti et al [34], and indicated that HS-SPME is efficient for compounds with the KH higher than 0.17 atm cm 3 /mol ( Table 1).…”
Section: Verify the Suitability To Hs-spme Techniquesupporting
confidence: 90%
“…Therefore, the constant of distribution estimated from physicochemical tables or by using the structural unit contribution method can anticipate trends in SPME analysis. The KH of the TBC-dimethylether, acetylacetone-PFB-oximes and TBBC-methyl-bis-oxime derivatives were 1.3, 71 52 and atm cm 3 /mol, which were in agreement with that reported by Pacenti et al [34], and indicated that HS-SPME is efficient for compounds with the KH higher than 0.17 atm cm 3 /mol ( Table 1).…”
Section: Verify the Suitability To Hs-spme Techniquesupporting
confidence: 90%
“…Modern high-performance liquid chromatography (HPLC) with UV detection (Bourque et al, 1994;Fujii et al, 1999;Inoue et al, 1991), gas chromatography (GC) with flame ionization detection (Chakroum et al, 2008;Kataoka et al, 1991), and high-performance chromatography with mass spectrometry (Pacenti et al, 2008;Marais and Laurens, 2005) were performed for evaluating styrene. The level of styrene present in food and drinks depend on many factors such as heat, pH, fats, and the time of storage.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods, such as liquid-liquid extraction (LLE) 9 and solid phase extraction (SPE), 10 are tedious, time-consuming and consume large amounts of solvent. Recently, new microextraction techniques such as solid phase microextraction (SPME), 11,12 and liquid phase microextraction (LPME) 13 have been developed because they are simple, fast and solvent-free or with less consumption of organic solvent. Among these techniques, liquid phase microextraction using a hollow fiber (HF-LPME) 14 provides a simple, effective, economic and environmentally benign extraction method.…”
Section: Introductionmentioning
confidence: 99%